Detection of adjective compound word in Malay language using enhanced syntactic rules / Zamri Abu Bakar ...[et al.] - Abu Bakar, Zamri; Kamal Ismail, Normaly; Anuar, Nurhilyana; Idris, Aminatul Solehah (UiTM Cawangan Perlis, 2021)
Compound word is defined as combination two or more words and it will produce a new meaning. Generally, compound word is existed in many languages such as English, Mandarin, Arabic and others. Although, there are discussion of existing methods to detect compound word yet some limitations on detecting Malay compound word. Thus, this study is done to improve accuracy towards adjective compound words. Training data is used in this study was Malay story books. Digitization data of Malay story book is used in this study. Then, the pre-processing method involved tokenization, stemming, bi-gram and part-of-speech (POS) tagging has been applied to produce the candidate compound word. Applying the enhanced syntactic rules shown the precision result is 70.3% through this study. Thus, this study will contribute to the academic research in improvise the issues on searching and document summarization application.